Analisa Faktor-Faktor Perceived Service Quality dalam Bidang Aviasi terhadap Passenger Loyalty melalui Passenger Satisfaction dan Passenger Complaint pada Penumpang Batik Air Tujuan dari dan ke Surabaya - Richardo Evan Wongharyono; Ronald Ronald; Amelia Amelia (IPM2KPE, 2024)
This research is intended to find factors that influence Passenger Loyalty through Passenger Satisfaction and Passenger Complaint of Batik Air customers in Surabaya. This research provides benefits for the aviation industry in Indonesia, especially to create customer loyalty to an airline in order to be able to survive in the market in the long term.This study is causal with quantitative methods and uses the Amos 22.0 application to assist the processing of primary data from 200 Batik Air customers in Surabaya which was collected using the Snowball Sampling Technique. In this study it was found that customers will be loyal to a brand influenced by Customer Satisfaction which is most influenced by Safety and Security, Reliability, Connectivity, Information Service, Accessibility, Operation Schedule, Comfort, Ticket service, and Personalized Services. Consumers' perception that airplanes with low prices do not prioritize safety, but from this research it can be broken because Batik Air is significant in the Safety and Security variable. eywords: Accessibility, Comfort, Connectivity, Information Service